The Effect of Liquidity, Solvability and Assets on the Profitability of Women Entrepreneurs - Rita Indah Mustikowati; Hery Pratikto (AFRE (Accounting and Financial Review), 2022)
In recent years, several researchers have criticized the diversity of gender in influencing the financial performance of companies. Despite providing high benefits and variety in the field of entrepreneurship, female entrepreneurs continue to be seen as an insignificant factor in entrepreneurship due to the dominance of male entrepreneurs. The purpose of this study was to analyze the financial performance of SMEs in Malang Regency. Data were collected from 100 female entrepreneurs and analyzed using multiple linear regression. Data was collected by using a simple random sampling technique. The results showed that liquidity and solvency had no significant effect on the profitability of women entrepreneurs in Malang Regency, while assets had a significant influence on the profitability of women entrepreneurs in Malang Regency. This finding seeks to allocate sources of funds in order to carry out investment activities, provide liquid assets so that they do not lose if at any time they are disbursed, provide guarantees of their own capital to pay off long-term debts, utilize all assets owned in order to increase income.